2014
DOI: 10.4236/jct.2014.513125
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetic Acid (DCA)-Induced Cytotoxicity in Human Breast Cancer Cells Accompanies Changes in Mitochondrial Membrane Permeability and Production of Reactive Oxygen Species

Abstract: Cancer cells utilize cytosolic glycolysis for their energy production even in the presence of adequate levels of oxygen (Warbug effect) due to mitochondrial defects. Dichloroacetic acid (DCA) shifts cytosolic glucose metabolism to aerobic oxidation by inhibiting mitochondrial pyruvate dehydrogenase kinase (PDK) and increasing pyruvate uptake. Therefore, DCA has potential in reversing the glycolytic metabolism defect in cancerous cells. DCA is also known to induce apoptosis in a number of cancer cell lines, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…As DCA-mediated increase in ROS production is known to induce oxidative cellular damage and apoptosis in breast cancer and myeloma cells 36 , 39 , we investigated whether treatment of PGL cells with DCA was associated with promotion of apoptosis. As indicated by flow cytometry evaluation of Annexin-V staining, DCA treatment resulted in a significant induction of apoptosis in both cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As DCA-mediated increase in ROS production is known to induce oxidative cellular damage and apoptosis in breast cancer and myeloma cells 36 , 39 , we investigated whether treatment of PGL cells with DCA was associated with promotion of apoptosis. As indicated by flow cytometry evaluation of Annexin-V staining, DCA treatment resulted in a significant induction of apoptosis in both cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DCA has shown a promising role as cancer treatment, since it appears more tolerated than standard cytotoxic chemotherapy 39 . In this regard, an open-label, phase 1 trial using oral DCA in patients with recurrent glioblastoma showed that chronic oral assumption of DCA is a feasible and well-tolerated drug treatment in patients with malignant gliomas 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichloroacetic acid (DCA) is an analogue of acetic acid, and has a broad range of therapeutic applications in various diseases, including lactic acidosis, topical chemoablation, and cancers, due to its ability to inhibit the enzyme pyruvate dehydrogenase kinase . DCA can not only decrease mitochondrial membrane potential, but also enhance ROS levels in cancer cells, leading to cytotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…Pyruvate dehydrogenase kinase (PDK) 1 is a key factor in the connection between glycolysis and mitochondrial OXPHOS and is highly expressed in most tumor cells. 5 , 6 Tumor cells with high expression of PDK1 have anti-apoptotic activity. 7 , 8 PDK1 phosphorylates pyruvate dehydrogenase (PDH) to inhibit its activity, thus reducing available pyruvate for mitochondrial metabolism.…”
Section: Introductionmentioning
confidence: 99%